2018
DOI: 10.5500/wjt.v8.i4.110
|View full text |Cite
|
Sign up to set email alerts
|

Renal transplants from older deceased donors: Is pre-implantation biopsy useful? A monocentric observational clinical study

Abstract: AIMTo compare survival of kidney transplants from deceased extended criteria donors (ECD) according to: (1) donor graft histological score; and (2) allocation of high score grafts either to single (SKT) or dual (DKT) transplant.METHODSRenal biopsy was performed as part of either a newly adopted DKT protocol, or of surveillance protocol in the past. A total 185 ECD graft recipients were categorized according to pre-implantation graft biopsy into 3 groups: SKT with graft score 1 to 4 [SKT(1-4), n = 102]; SKT wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…The usefulness of preimplantation biopsy as a predictive tool for graft survival has not been validated yet and some studies discuss its value for the assessment of the quality of organs from ECD [ 15 , 18 - 20 ]. In our case, all the grafts had a preimplantation biopsy and only those with a global score <7 were accepted.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of preimplantation biopsy as a predictive tool for graft survival has not been validated yet and some studies discuss its value for the assessment of the quality of organs from ECD [ 15 , 18 - 20 ]. In our case, all the grafts had a preimplantation biopsy and only those with a global score <7 were accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent Italian studies on the utility of pre-implantation biopsy in allocating ECD kidneys[4,55] concluded that histological evaluation was not superior to donor clinical evaluation in allocating ECD kidneys either as a single kidney or as a dual kidney transplant. The authors concluded that, according to their experience, the histological score poorly evaluates the donor kidney quality.…”
Section: Histological Evaluation Of Donor Kidneysmentioning
confidence: 99%
“…Histopathological evaluation of the donor kidney via biopsy is an important component of the comprehensive evaluation, especially for ECD evaluation [4,5]. The pre-implantation biopsy is performed not only to evaluate the potential chronic changes in renal structure, but also to assess ischemic injury in the donated kidney [11]. Hypothermic mechanical perfusion (HMP) has been shown to mitigate DGF by removing residual renal microthrombi, dredging renal micro vessels and provide measures to assess renal function [6,7,12].…”
Section: Introductionmentioning
confidence: 99%